Improved nutritional status may promote an "asset protection" reproductive strategy in male rock lizards. (20th August 2021) - Rodríguez-Ruiz, Gonzalo; Ortega, Jesús; López, Pilar; Salvador, Alfredo; Martín, José
Abstract: Investing in the current reproduction requires diverting energy resources from other metabolic functions, which may compromise future reproduction and lifespan. To solve this trade-off, an individual may consider its labile state to decide how much to invest in current reproduction. We tested experimentally whether the "state quality" of male rock lizards influences their reproductive strategies. To improve the nutritional status of males before the mating season, we captured and supplemented experimental males ( N = 20) with dietary vitamin D3 (an essential nutrient for lizards) and had a control group of males ( N = 20). Then, we released all these males and females ( N = 31) in a large semi-natural outdoor enclosure where lizards could interact and mate freely during the mating period. Activity levels of males did not vary between treatments, but supplemented males started fewer intrasexual agonistic interactions and made fewer mating advances to females. When the mating season ended, we incubated eggs laid by females to obtain the offspring and estimated the paternity of males using DNA microsatellites. Supplemented males sired fewer offspring than control males. These results suggest that vitamin D3 supplemented males used a low risk/less costly mating strategy to protect their assets (i.e., vitamin D reserves), but that still resulted in "some" current reproductive success, while likely increasing longevity and the expected future total reproductive success. Abstract : A wise investment! When an animal has enough resources for a long life and have many descendants, it should protect its reproductive asset by investing carefully. To live long enough to produce many descendants, it needs to balance resources allocated towards health or reproduction. Instead of making one single large investment to get more mates, to save resources well fed healthy male lizards reduce fights with other males and additional mating attempts, ensuring survival and future reproduction.